(untitled) (Third Sector Social Economic Review, 2026)
Eye-tracking technology is an experimental research method that enables the real-time and objective examination of visual attention in relation to cognitive processes and decision-making. Although its use in business research has increased in recent years, methodological challenges related to experimental design, sample selection, data quality, and analysis remain substantial. Moreover, studies providing systematic methodological guidance tailored specifically to business research contexts are limited. This study aims to offer a comprehensive methodological framework for the use of eye-tracking technology in business research. It presents a literature review of eye-tracking applications across core business functions, including finance, marketing, production, and management, and discusses key technological features and critical considerations for experimental design. In addition, a sample eye-tracking application in a financial decision-making context is presented to illustrate the practical implementation of the proposed framework. Overall, this study offers systematic and practice-oriented methodological guidelines for conducting eye-tracking experiments in business research.